Study of hydration skin by the cosmetics emulsions for xerosis and their stability by rheology (Revista Brasileira de Ciências Farmacêuticas, 2007)
NI (nonionic) and LC (liquid crystal) emulsions were developed, and their rheological parameters were evaluated. Also, the hydrating effect of NI and LC emulsions was tested among women with 20 ± 2 years, as well as NI emulsions among women with 70 ± 7 years of age. The results showed that the emulsions were stable and they had a pseudoplastic behavior and apparent thixotropy. The data revealed the best rheological profile of the NI emulsion with the lowest pour point (13.57 ± 3.19 Pa) and the highest spreadability (4.99 ± 0.54 mm²/g). There was no significant difference in hydration between NI and LC emulsions (16.0 ± 5.1%; 14.2 ± 5.5%) among younger women. However, hydration among elderly women was of 13.1 ± 5.6% for NI emulsion, revealing that it was significantly lower in this group when compared to the younger one. These data revealed the importance of rheological evaluation as a factor of choice among similar cosmetic formulations. Age bracket selection also proved to be very important in the assessment of skin hydration by cosmetic products.